Why Integrate Evolutionary and Functional Aspects in Bird Studies in Converted Habitats? - Ines Jacoboski, Lucilene (International Ornithology, 2018)
This essay argues for integrating evolutionary and functional perspectives in bird studies within converted habitats. It highlights how behavior, morphology, and phylogeny interact under land-use change.
Keywords: Bird Studies; Converted Habitats; Morphology; Phylogeny; Land-Use Change